6x-6z=6+5y

Simple and best practice solution for 6x-6z=6+5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-6z=6+5y equation:


Simplifying
6x + -6z = 6 + 5y

Solving
6x + -6z = 6 + 5y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6z' to each side of the equation.
6x + -6z + 6z = 6 + 5y + 6z

Combine like terms: -6z + 6z = 0
6x + 0 = 6 + 5y + 6z
6x = 6 + 5y + 6z

Divide each side by '6'.
x = 1 + 0.8333333333y + z

Simplifying
x = 1 + 0.8333333333y + z

See similar equations:

| 10(-2x+1)=-14(x+2)+39-6x | | c(x)=6X+50 | | 4y-2y+4=26 | | ln(19)-ln(5)=ln(x+2) | | 4.8X+43.1=22.7-5.4X | | (37b-3)-9(4b+2)=-4 | | 0.3(x+10)+x=6.9+0.3x | | -2(w-4)=12 | | -(6-4a)-(20+3a)-3=-(5-6a)+(-a)+4 | | -2-2(w-4)=12 | | 1+126t-t^3=0 | | x^2=24+5x | | -(6-4a)-(20+3a)-3=-5(5-6a)+(-a)+4 | | 31-3y=4 | | (2x-3y)dx-(3x+2y)dx=0 | | (x^2)(7)= | | (3x)(92x)=13/9 | | 23/ | | -15p-5(3-5p)=5(p-4)-40 | | -x/52 | | -10/14 | | x^2-2px+p^2-1=0 | | 4+3x+0x^2+0.5x^3=0 | | 2a^2-15a+12=0 | | 9+18Z-7=9Z+50-7Z | | 2y^2-26y=0 | | -6(x+3)+4x+5=6x+12 | | 4-x^2-2x=35 | | 60-2x=81+x | | 25x^2y^4+10xy^3-15x^2y^5=0 | | 6x^2+15x-7=0 | | f=1/2(hp) |

Equations solver categories